An angel for Solomon Singer - Rylant, Cynthia; Catalanotto, Peter (New York : Orchard Books, 1992)
A lonely New York City resident finds companionship and good cheer at the Westway Cafe where dreams come true.
"A Richard Jackson book."
G9
Keywords: Loneliness -- Fiction; Wishes -- Fiction; Restaurants -- Fiction; New York (N.Y.) -- Fiction